2018
DOI: 10.1021/acscatal.8b02437
|View full text |Cite
|
Sign up to set email alerts
|

Photoexcited Electrons Driven by Doping Concentration Gradient: Flux-Prepared NaTaO3 Photocatalysts Doped with Strontium Cations

Abstract: Electron–hole recombination always competes with desired reactions on semiconductor photocatalysts. Reducing recombination probability is essential for increasing the quantum efficiency of the reactions. Previous studies demonstrated that doping with lanthanoid or alkaline-earth metal cations reduced recombination probability in NaTaO3 photocatalysts for artificial photosynthesis. The motivation behind this study was to reveal how the guest metal cations reduced recombination probability. NaTaO3 photocatalysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 33 publications
4
45
0
Order By: Relevance
“…The water splitting rate was examined over the four Srcontaining photocatalysts (Sr concentration=2 mol %) prepared in the NaCl flux . H 2 and O 2 production rates are plotted in Figure as a function of integrated absorbance change evaluated with the spectra shown in Figure (i.e., the photoexcited electron population).…”
Section: Water Splitting Rate Compared With Photoexcited Electron Popsupporting
confidence: 62%
See 1 more Smart Citation
“…The water splitting rate was examined over the four Srcontaining photocatalysts (Sr concentration=2 mol %) prepared in the NaCl flux . H 2 and O 2 production rates are plotted in Figure as a function of integrated absorbance change evaluated with the spectra shown in Figure (i.e., the photoexcited electron population).…”
Section: Water Splitting Rate Compared With Photoexcited Electron Popsupporting
confidence: 62%
“…A more recent study further evidenced the essential role of the graded composition . NaTaO 3 photocatalysts were doped with Sr cations through crystallization in molten NaCl flux maintained at 1423 K. Chemical composition and simultaneous doping to form the NaTaO 3 –Sr(Sr 1/3 Ta 2/3 )O 3 solid solution were checked and confirmed.…”
Section: Nanoscale Architectures For Driving Electron Excitationmentioning
confidence: 95%
“…This concentration dependence is similar to the one that electron population in Sr-NTO-SS increased with increasing Sr concentration and then decreased at Sr concentrations above 1.8 mol%. 15,38 It should be noted that the blue shift of approximately 0.1 eV in the lower concentration region is comparable to the increase of the band gap energy (~0.1 eV) by Sr-doping. 15,38 Meanwhile, the higher doping amount (> 3 mol%) results in the red shift of the PL peak, possibly due to delocalization of the excited states and/or involvement of deeper trap states caused by crystal deformations and surface reconstructions.…”
Section: Resultsmentioning
confidence: 85%
“…15,38 It should be noted that the blue shift of approximately 0.1 eV in the lower concentration region is comparable to the increase of the band gap energy (~0.1 eV) by Sr-doping. 15,38 Meanwhile, the higher doping amount (> 3 mol%) results in the red shift of the PL peak, possibly due to delocalization of the excited states and/or involvement of deeper trap states caused by crystal deformations and surface reconstructions. 28,39 It was suggested that excess K-doping (> 5 mol%) creates defect states in K-doped NaTaO3, thus lowering the photocatalytic activity.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation